Serum resistance and lipopolysaccharide of haemophilus ducreyi - Jardine, Jocelyn. Leonie (My University, 1990)
The pathogenesis of Haemophilus ducreyi, the aetiological agent of chancroid' is poorly understood. An ability to resist killing by pooled normal human serum (PNHS) appears to contribute to the virulence of several Gram-negative bacteria, influenced by their lipopolysaccharide (LPS) in certain cases. The aim of this investigation is to measure the degree of serum resistance in clinical strains of H. ducreyi, and to determine whether their LPS plays a role in this serum resistance.
A dissertation submitted to the Faculty of Medicine, University of the VVitwatersrand, Johannesburg, in fulfilment of the requirements for the degree Master of Science. 1990
Keywords: Haemophilus ducreyi; Serum; Lipopolysaccharides